2018
DOI: 10.2337/db18-0500
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Regulation of Pigment Epithelium-Derived Factor (PEDF): An Exome-Chip Association Analysis in Chinese Subjects With Type 2 Diabetes

Abstract: Elevated circulating levels of pigment epithelium-derived factor (PEDF) have been reported in patients with type 2 diabetes (T2D) and its associated microvascular complications. This study aimed to 1) identify the genetic determinants influencing circulating PEDF levels in a clinical setting of T2D, 2) examine the relationship between circulating PEDF and diabetes complications, and 3) explore the causal relationship between PEDF and diabetes complications. An exome-chip association study on circulating PEDF l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…SERPINF1 regulates pancreatic vasculature development, and its deficiency causes atypical hyperplastic phenotypes in the pancreas [36]. While elevated levels of SERPINF1 have been reported in patients with diabetes and associated microvascular complications [37], a study showed that SERPINF1 was a critical negative regulator of tumor invasion in the pancreas [36]. Our data suggested that, compared to diabetic controls, the plasma level of SERPINF1 was decreased in PDAC.…”
Section: Discussionmentioning
confidence: 52%
“…SERPINF1 regulates pancreatic vasculature development, and its deficiency causes atypical hyperplastic phenotypes in the pancreas [36]. While elevated levels of SERPINF1 have been reported in patients with diabetes and associated microvascular complications [37], a study showed that SERPINF1 was a critical negative regulator of tumor invasion in the pancreas [36]. Our data suggested that, compared to diabetic controls, the plasma level of SERPINF1 was decreased in PDAC.…”
Section: Discussionmentioning
confidence: 52%
“…Mutations of this gene are also detected in osteogenesis imperfecta, type VI [39,40]. Individuals suffering from type II diabetes have increasing circulating level of PEDF, confirmed a strong association with this gene at genome-wide significance [41,42]. In cancerous diseases, SERPINF1 functions as a tumor suppressor in cervical cancer, which is downregulated by TXNDC5, resulting in stimulating cell migration, vasculogenic mimicry and angiogenesis [43].…”
Section: Discussionmentioning
confidence: 91%
“…Cheung et al. performed an exome-chip association analysis in Chinese subjects with type 2 diabetes ( 46 ). They noticed elevated circulating pigment epithelium-derived factor levels were associated with increased risks of DN and sight-threatening diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptomic signatures and the action of the drugs BRD-K04548931 and BRD-K41652870 on renal epithelium cell lines (HA1E) are shown in Supplementary Figure 3. (46). They noticed elevated circulating pigment epithelium-derived factor levels were associated with increased risks of DN and sight-threatening diabetic retinopathy.…”
Section: Drug Perturbation Of the Transcriptome Datamentioning
confidence: 99%